An investigation of occupational therapy services for people who are dying in Western Australia - Keesing, Sharon (Curtin University, 2011)
BACKGROUND In Western Australia (WA) little is known about the occupational needs of people at the end of life and their primary carers. The role of occupational therapy (OT) in addressing these needs is not documented and the palliative services provided by occupational therapists (OTs) are poorly understood. To address this gap there were several aims of the study. First, to ascertain the number of OTs working in this field across a range of service delivery locations in WA. Second, to explore the self-care, leisure and productive occupations of dying people through carers’ reports of their daily experiences and reflections on their occupational needs. Finally, to understand the role of OT in meeting these needs, this research aimed to document the unique kinds of services provided by Western Australian OTs who provide palliative care to a range of service delivery locations in WA.METHODS A mixed methods approach in two stages was used to achieve the research objectives. In stage one an email survey was conducted to identify preliminary data that informed the substantive component of the research. This survey determined the number of OTs providing services to people who were dying in WA and the types of services provided, and then calculated a ratio with the number of people dying from conditions considered amenable to palliative care. In stage two, semistructured interviews were used to gather information from carers (n = 10 metropolitan, n = 4 rural) and occupational therapists (n = 13 metropolitan, n = 5 rural). Data were analysed qualitatively using grounded theory to develop categories. Themes were defined using the constant comparison method.RESULTS The survey of OTs indicated that 6.15 full time equivalent OTs were employed to provide palliative services in Western Australia. Compared with the number of people who died from conditions considered amenable to palliative care over a one year period in WA, this is represented as a ratio of one occupational therapist per 875 people. Two key themes emerged from the interviews with carers, disengagement from occupations with resultant occupational deprivation and disempowerment. The interviews with OTs illustrated that the occupational needs of dying people and their carers were not addressed adequately in palliative care service delivery. Furthermore OTs have limited opportunities to both contribute to the care of dying people and address their core business of ‘occupation’.CONCLUSION The research demonstrated that Western Australian OTs have limited opportunity to address the occupational needs of people at the end-of-life and their primary carers. Palliative services currently focus on pain and symptom management for their clients. While this is to a large extent understandable, carers also reported the importance of engaging in meaningful and satisfying occupations throughout the palliative period for the dying person and themselves. Occupational Therapists are well placed to address these needs but face a number of personal and organisational challenges in achieving this goal. For change to occur, issues of education and professional development, organisational and policy management would need to be addressed.